Understanding Chemistry Through Virtual Laboratory Class X Odd Semester MAN 2 Rembang - Sholeh Sholeh (Journal of Education and Teaching Learning, 2022)
This research was conducted to test the success of student learning through the media applied, namely a virtual laboratory in chemistry lessons at MAN 2 Rembang. This study uses a qualitative approach with the method of content analysis of objects during the use of a virtual laboratory. The results of the study found that the use of a virtual laboratory in chemistry learning was an effective thing to do on the daily learning outcomes (KKM 70) of students. The effectiveness of this virtual laboratory is due to an increase in student learning outcomes and understanding of chemistry subjects. When viewed from the discipline of collecting chemistry class assignments, using a virtual laboratory also reaped good and positive results, even in class X IPA-2 who submitted assignments in the 100% percentage, meaning the category was complete. This means that the stimulus from the virtual laboratory is able to make learning effective, attractive and increase student motivation in doing assignments in chemistry subjects.